Morphology of the Denisovan phalanx closer to modern humans than to Neanderthals - Bennett, E. Andrew (Sci Adv, 2019)
A fully sequenced high-quality genome has revealed in 2010 the existence of a human population in Asia, the Denisovans, related to and contemporaneous with Neanderthals. Only five skeletal remains are known from Denisovans, mostly molars; the proximal fragment of a fifth finger phalanx used to generate the genome, however, was too incomplete to yield useful morphological information. Here, we demonstrate through ancient DNA analysis that a distal fragment of a fifth finger phalanx from the Denisova Cave is the larger, missing part of this phalanx. Our morphometric analysis shows that its dimensions and shape are within the variability of Homo sapiens and distinct from the Neanderthal fifth finger phalanges. Thus, unlike Denisovan molars, which display archaic characteristics not found in modern humans, the only morphologically informative Denisovan postcranial bone identified to date is suggested here to be plesiomorphic and shared between Denisovans and modern humans.